Captivating Your Class : Effective teaching skills - Philpott, Joanne (London : Continuum, 2009)
The chapters in this book cover creating independent students, encouraging reflective learners, extending students thinking, revision, the next steps, and more.
Includes bibliographical references and index.
Keywords: High school teaching -- Great Britain; Effective teaching -- Great Britain; A-level examinations -- Great Britain; Education